INTEGRATION OF MARRIAGE LAW AND CUSTOMARY LAW WITHIN THE INDONESIAN LEGAL FRAMEWORK - Suriadiata, Irpan (fakultas hukum universitas PGRI Semarang, 2025)
Indonesia utilizes a pluralistic legal system where national and customary laws intersect, especially in areas like marital law. This study explores the relationship between national marital law and customary practices, highlighting the challenges in harmonizing the two. Key issues include inconsistencies in legal enforcement, clashes between the rigidity of national law and the flexibility of customary law, and limited understanding of customary systems among legal practitioners. To overcome these challenges, the study recommends strengthening the legal recognition of customary law, empowering traditional institutions in conflict resolution, and fostering ongoing dialogue between the state and indigenous communities. These steps are essential to create a more integrated legal system. Ultimately, the study seeks to contribute to a fair and culturally respectful marital law framework in Indonesia—one that protects individual rights while honoring the nation's diverse traditions. This approach aims to ensure both legal certainty and cultural sensitivity in the Indonesian legal landscape